Development of Project-Based ICT and Media E-Modules for Learning During the Covid-19 Pandemic - Basuki, Nur (Journal of Community Research and Service, 2022)
Media courses and learning are courses that describe the basic concepts of knowledge, theoretical understanding, and practice of effective and efficient learning media in the teaching and learning process. The e-module was developed using the Dick and Carey (2005) model which has 10 steps, namely: 1) the stage of the need and determining general goals, 2) conducting a learning analysis, 3) identifying behaviors and early learners, 4) writing specific learning objectives, 5) compiling learning outcome tools, 6) developing learning strategies, 7) selecting and developing learning materials, 8) implementing and implementing formative evaluations, 10 carrying out evaluations, and carrying out evaluations. Modules that have passed the development stage that needs to be evaluated. The purpose of this development research is to produce e-modules for media and information and communication technology courses for learning in the Department of Mechanical Engineering Education, Faculty of Engineering, State University of Medan. The results of the development, based on the results, that the validity of the e-module material obtained a score of 92 which was in the very good category, the validity of the learning design was 93.91, the media aspect was 90.00. Student assessment 85.77. In conclusion, the E-module for media and typewriting courses for learning is suitable for use in classroom or online learning during the COVID-19 pandemic. The implication of this research result is used as input for lecturers. Fixing yourself is related to the problems that have been carried out and student achievement that has been achieved by paying attention to appropriate learning methods to improve student learning achievement.